2018
DOI: 10.1364/josaa.35.00b347
|View full text |Cite
|
Sign up to set email alerts
|

Age, pupil size differences, and color choices for the “dress” and the “jacket”

Abstract: The color identification responses to photographs of #thedress (white/gold and blue/black) and a jacket (white/blue and green/black, and teal) reveal obvious individual differences in color perception. To explore possible association between pupil size/retinal illuminance and color perception, we recorded the pupil diameters of participants shown 22 uniformly colored (generated from the RGB values using a laptop LCD display) screens followed by photographs of #thedress and jacket. We analyzed (a) pupil size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Pupil diameter also decreased with age in both genders (R = −0.537, p = 0.000 for males and R = −0.208, p = 0.006 for females). This is consistent with previous findings [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Pupil diameter also decreased with age in both genders (R = −0.537, p = 0.000 for males and R = −0.208, p = 0.006 for females). This is consistent with previous findings [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…The Jacket has been described to be perceived as green and gold or white and blue (Witzel, O’Regan, et al., 2017). Previous research found that The Jacket is a phenomenon different from The Dress (Vemuri et al., 2018; Witzel, O’Regan, et al., 2017). For instance, Witzel, O’Regan, et al.…”
Section: The Present Studymentioning
confidence: 97%
“…The Jacket has been described to be perceived as green and gold or white and blue . Previous research found that The Jacket is a phenomenon different from The Dress (Vemuri et al, 2018;. For instance, found that the perceived colors of The Dress were more influenced by assumed illumination than were the perceived colors of The Jacket, particularly relating to whether short-wavelength daylight or long-wavelength artificial light was assumed (see also Winkler et al, 2015).…”
Section: The Present Studymentioning
confidence: 99%
“…People disagree strongly about the colour of the depicted dress: some see a white dress with gold trim, while others see a deep blue dress with black trim. Low-level factors may contribute to these large individual differences, including differences in pre-retinal filtering and spectral sensitivities (Brainard & Hurlbert, 2015;Rabin, Houser, Talbert, & Patel, 2016;Vemuri, Srivastava, Agrawal, & Anand, 2018), although a twin study indicates individual differences in perceived dress colour are mostly due to environmental rather than genetic factors (Mahroo et al, 2017). The explanation supported by most research is that people make different estimates of the lighting conditions in this picture, and so when colour constancy mechanisms discount the lighting, very different estimates are produced of the material colour of the dress (Brainard & Hurlbert, 2015).…”
Section: Illumination Colour: #Thedressmentioning
confidence: 99%